Human Resources Management Implementation Impact on Job Satisfaction and Employee Loyalty an Overview - Mukhlis Catio, 2Denok Sunarsi, Munawaroh,Udi Iswadi, Dina Satriani, Achmad Rozi , Agus Purwanto (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research reveals the relationship between the implementation of human resource management (HRM) with job satisfaction, and disobedient employees by explaining the relationship between these three variables. Job satisfaction has an important impact in disobedient employees because they will immediately resign when their job satisfaction turned low. The results showed that HRM practices had a positive and significant correlation with job satisfaction. On the other hand, HRM practices and job satisfaction are negatively